Animal-sourced foods improve child nutrition in Africa - Khonje, Makaiko G; Qaim, Matin (National Academy of Sciences, 2024)
Child undernutrition remains a widespread public health problem in the Global South, especially in Africa. Childhood stunting-meaning linear growth retardation-is a comprehensive and commonly used indicator of chronic child undernutrition and is mostly the result of insufficient nutrient intake, among other factors. Previous research showed that the consumption of animal-sourced foods (ASF), including meat, dairy, eggs, and fish, is associated with lower rates of child stunting, but reliable evidence for Africa is scant. In Africa, average ASF consumption is low. We use representative panel data from five African countries-Ethiopia, Malawi, Nigeria, Tanzania, and Uganda-with over 32,000 observations from children aged 0 to 5 y to show that ASF consumption increases mean child height-for-age Z-scores (HAZ) by 0.30 (P < 0.01) and reduces the likelihood of stunting by 6.8 percentage points (P < 0.01), after controlling for confounding factors. The child nutritional benefits of diets containing ASF are larger than those of purely plant-based diets. Nutritious plant-based foods, such as fruits, vegetables, and legumes, can provide most of the nutrients required and also have positive effects on HAZ, but they are sometimes not available and accessible in sufficient quantities all year round, especially in rural areas. Given the large environmental footprints of livestock farming, initiatives to make food systems more sustainable often call for a strong reduction in ASF consumption. While ASF consumption should be reduced where consumption quantities are high, our results suggest that poor households' access to ASF in Africa should be further improved to help reduce child undernutrition. Virology and AIDS Abstracts